Dosis de magnesita en el cultivo de brócoli (Brassica Oleracea) variedad royal favor f - 1 hyb provincia de Lamas - San Martín - Montalvo Pisco, Tatiana (2012)
The demand for broccoli is increasing worldwide, especially in developed countries, due to changes in eating habits. Within this context, the export possibilities appear as an important alternative for horticultural producers. The cultivation of this product is made possible thanks to its soil and climate requirements, which allows for great adaptability as: high pH as close to neutral. The most advisable to make better use of soil nutrients by the plant range is between 6.0 and 6.8, as it is a little acidity tolerant plant. It grows in a wide range of soils but are preferable loams, clay loam or silt loam, deep, with good organic content and good water holding capacity. In heavy soils it is necessary to carry out work of internal and surface drainage. In addition to developing a suitable plant needs cold, wet climates; the optimal average temperature is between 12 and January 6 ° C, with average lows of 5 degrees. Temperatures above 20 ° C cause the formation of irregularities in the inflorescences, causing reduced compaction thereof, determinant of product quality. On the other hand temperatures near 0 ° C to stop the growth of the plant. For the vegetative development requires a relative humidity of 80% with a minimum of 70%. Broccoli can be grown adequately in areas between 2,200 and 2,800 meters The recent commercial development of broccoli in the world, promoted by an increase in consumption, it is common to other Latin American countries. Such is the case of Chile, Ecuador and Peru. There are no reliable statistics on area and production of this crop is estimated a total of about 100 000 ha planted worldwide. Currently, the US is the largest producer and consumer of broccoli with approximately 50 000 ha planted. In America, broccoli is also grown in Mexico, Guatemala, Chile, Ecuador and Peru. In Europe, especially in Italy, Spain, France, UK and the Netherlands. Other producing countries of this vegetable are South Africa, Japan and Taiwan. The production volume of growing broccoli in Ecuador is 10.4 TM and TM Peru is 6.0, which has a range of export 1-10 TM (Peru) and 10,000 MT in Ecuador. Among the five member countries of the Commonwealth, only Ecuador and Peru produce broccoli. In the export market, Ecuador has great presence, with potential for the European Community market. Peru has a minimal presence for this product and the Community trade, it is also negligible.